The potential and controversy of targeting STAT family members in cancer. (February 2020) - Verhoeven, Yannick; Tilborghs, Sam; Jacobs, Julie; De Waele, Jorrit; Quatannens, Delphine; Deben, Christophe; Prenen, Hans; Pauwels, Patrick; Trinh, Xuan Bich; Wouters, An; Smits, Evelien L.J.; Lardon, Filip; et al.
Abstract: The Signal Transducer and Activator of Transcription (STAT) family of proteins consists of transcription factors that play a complex and essential role in the regulation of physiologic cell processes, such as proliferation, differentiation, apoptosis and angiogenesis, and serves to organize the epigenetic landscape of immune cells. To date, seven STAT genes have been identified in the human genome; STAT1, STAT2, STAT3, STAT4, STAT5a, STAT5b and STAT6. They all account for diverse effects in response to extracellular signaling proteins, mainly by altering gene transcription in the effector cells. Members of the STAT family have been implicated in human cancer development, progression, metastasis, survival and resistance to treatment. Particularly STAT3 and STAT5 are of interest in cancer biology. They are currently considered as oncogenes, but their signaling is embedded into a complex and delicate balance between different (counteracting) transcription factors, and thus, in some contexts they can have a tumor suppressive role. Assessing STAT signaling mutations as well as screening for aberrant STAT pathway activation may have a role to predict sensitivity to immunotherapy and targeted STAT inhibition. In the present comprehensive review of the literature, we discuss in-depth the role of each STAT family member in cancer, assemble cutting-edge information on the use of these molecules as potential biomarkers and targets for treatment, and address why their clinical implementation is controversy.